Factors Associated with Drug Use in Urban and Rural Adolescents Attending School in the Canton of Milagro-Ecuador - Campos, Grecia Elizabeth Encalada; Romero-Urrea, Holguer Estuardo; Almeida Monge, Elka Jennifer; Benavides, Janeth Rosario Medina; Moreta, Carmen Azucena Yancha; Guadalupe, Andres Montalvan; Encalada, Johanna Valeria Caranqui (Journal of Posthumanism, 2025)
The issue of substance abuse among adolescents in both urban and rural regions of Latin America has emerged as a pressing concern on a global scale. This phenomenon is driven by a complex interplay of psychosocial and economic factors, which have profound ramifications on individuals, communities, and societies. This study aims to examine the consumption of both licit and illicit substances among adolescents enrolled in educational institutions in both rural and urban areas of Milagro, Ecuador. The research employs a quantitative descriptive study design, enabling the comprehensive identification of social, economic, and psychological factors associated with drug abuse, both licit and illicit, among adolescents aged 12 to 18 years. A structured survey was validated by expert judgment and used as the information collection technique. The consumption patterns observed differed depending on the substance: 48.3% of the sample reported using cannabis and 48.3% heroin; in urban areas, drug use began at an early age of 15-16 years, except for cocaine, which was used at a later age: 16-17 years (64.6%). A comprehensive analysis reveals that drug use among school-going adolescents exhibits notable disparities between rural and urban regions. These variations are influenced by a multitude of factors, including drug availability, peer influence, risk perception, and accessibility to treatment resources. Addressing these disparities necessitates a comprehensive approach, entailing the formulation of prevention and treatment strategies that are tailored to the unique characteristics of each setting.